Photon - Axion Conversion Cross-Sections in a Resonant Cavity with general mode - Thuy, Dao Thi Le; Thuc, Le Nhu (Communications in Physics, 2012)
Photon-axion conversions in the resonant cavity with the general mode (TM$_{mn0}$) are considered in detail by the Feynman diagram method. The differential cross-sections are presented and numerical evaluations are given. It is shown that there is a resonant conversion for the considered process, in which the conversion cross-sections are much larger than those of the wave guide in the same conditions. Some estimates for experimental conditions are give from our results.